2020
DOI: 10.1200/jco.2020.38.15_suppl.3612
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of the MEK 1/2 inhibitor selumetinib (AZD6244, ARRY-142886 Hydrogen Sulfate) in adults with neurofibromatosis type 1 (NF1) and inoperable plexiform neurofibromas (PN).

Abstract: 3612 Background: NF1-related PN are locally invasive tumors characterized by increased activation of the RAS pathway causing significant morbidity including disfigurement, pain and functional limitations. Selumetinib has received breakthrough designation for NF1 PN based on phase I / II trials in children. We present results for the ongoing phase II study of selumetinib in adults with NF1 PN, which includes pharmacodynamic (PD) evaluation of serial tumor biopsies as well as functional/patient-reported outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…Searches were updated on 28 February 2021. undergoing screening (Figure 2). Nine reports from eight clinical trials have communicated results on the efficacy of novel targeted therapies in patients with NF1 and PNs (Table 1), [17][18][19][20][21][22][23][24][25] and eight of them have reported positive results. Nine trials are ongoing (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Searches were updated on 28 February 2021. undergoing screening (Figure 2). Nine reports from eight clinical trials have communicated results on the efficacy of novel targeted therapies in patients with NF1 and PNs (Table 1), [17][18][19][20][21][22][23][24][25] and eight of them have reported positive results. Nine trials are ongoing (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34] Out of the eight reports with positive results [17][18][19][20][21][22][23][24] (seven trials, one of them 18 with two strata reported separately 18,19 ), four have been published in peer-reviewed scientific journals 17,18,21,22 and the other four have been communicated as abstracts in international congresses. 19,20,23,24 All the studies included in the final analysis are single-arm phase I/II trials and included between 19 and 50 patients. Four of the trials with positive results were focused on children and adolescents [17][18][19]23,25 and three on adults with progressive/symptomatic inoperable PNs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations